SIKAP SPIRITUAL BERBASIS PENILAIAN DIRI TERHADAP MAHASISWA/I 4C PGMI UIN JAKARTA - Nur Elisa Addina; Nur Ana Diana; Keisya Aghnia Azami; Asma; Asep Ediana Latip (STKIP Subang, 2026)
Spiritual attitudes are one of the core competencies mandated in the national education curriculum, covering the dimensions of worship obedience, gratitude, prayer habits, and religious tolerance. This study aims to describe the spiritual attitude profile of students in class 4C of the Islamic Elementary School Teacher Education (PGMI) program at UIN Syarif Hidayatullah Jakarta based on a structured self-assessment instrument. Using a quantitative descriptive approach with total sampling, data were collected from 26 respondents through a Likert-scale questionnaire consisting of 10 statements covering four indicators: worship obedience, gratitude behavior, prayer habits, and religious tolerance. The results showed that students’ spiritual attitudes are in a very good category, with an average percentage of 90.6%. The highest percentage was recorded for the gratitude indicator at 100%, while the worship obedience indicator obtained the lowest percentage at 73%. These findings indicate that students already have good religious awareness in both academic and social life, although strengthening worship habits is still needed. This research contributes empirical evidence for the development of spiritual value-based learning assessment systems in Islamic higher education, particularly in reinforcing the spiritual dimension as an integral part of PGMI graduate competencies.